Song and political satire in the play, The Honourable MP (1987) - Rwafa, Urther (Taylor & Francis (Routledge), 2016)
Post-independence Zimbabwe, like some other countries in Africa, is a space disfigured by greedy, unfulfilled promises, corruption and political discontentment. The play, Honorable MP by Gonzo Musengezi subtly captures Zimbabwe's socio-political environment with its pot-bellied politicians who drain the national coffers, abuse young girls and abandon the electorate only to surface towards election time. Honourable MP (1987) uses the language of political satire and irony embedded in song and dramatic performance to move its story ahead. What this article analyses through song are levels of conceptualizing political greediness and intolerance that the play Honourable MP evokes. To analyse the songs in the play Honorable MP, Bhakhtin's (1984) theory of carnivalesque and laughter of the market-place are invoked to poke fun at and satirically bite at the spectacle of the excessive greed and consumerism of the powerful, and also mock some of the reactionary tendencies of the oppressed.